Portraying Teacher’s Metacognitive Knowledge to Promote EFL Young Learners’ Critical Thinking in Indonesia - Riwayatiningsih, Rika; Setyarini, Sri; Azmi Putra, Rahmat Agung (International Journal of Language Education, 2021)
Teaching English as a foreign language to young learners in Indonesia requires specific strategies because young learners have different characteristics compared to adults. It demands English teachers to have sufficient metacognitive knowledge to promote students’ critical thinking skills. Therefore, this research paper presents findings on teacher’s metacognitive knowledge to promote EFL young learners critical thinking. A case study was employed involving one class of fifth-grade students with one English teacher and three instruments to collect data, namely classroom observation, interview, and document analysis. The data analysis was done by referring to the theory of metacognitive knowledge and stages in promoting critical thinking in EFL classroom. The findings reveal that the teacher performed three types of metacognitive knowledge, such as person, task, and strategic knowledge. These types of knowledge determined teacher’s strategy in running the class. It was indicated from the teacher’s statement showing that metacognitive knowledge guide herself through what, why, and how to implement learning strategies and predict outcomes by considering students’ needs and characteristics. Consequently, the students were able to analyze, evaluate, compare, contrast, and construct new information from their previous knowledge and experience.Keywords: Critical thinking, EFL young learners, English language learning, Indonesian educational context, Teacher’s metacognitive knowledge